Influence of an Antioxidant Nanomaterial on Oral Tablet Formulation: Flow Properties and Critical Quality Attributes - Andrea C. Ortiz; Javiera Carrasco-Rojas; Sofía Peñaloza; Mario J. Simirgiotis; Lorena Rubio-Quiroz; Diego Ruiz; Carlos F. Lagos; Javier Morales; Francisco Arriagada (Antioxidants)
Antioxidant nanomaterials, particularly mesoporous silica nanoparticles (MSNs) functionalized with polyphenols, offer innovative solutions for protecting oxidation-sensitive components and enhancing bioavailability in pharmaceuticals or extending the shelf life of nutraceutical and food products. This study investigates the influence of MSNs functionalized with caffeic acid (MSN-CAF) on powder flow properties and their tableting performance. Aminated MSNs were synthesized via co-condensation and conjugated with caffeic acid using EDC/NHS chemistry. Antioxidant capacity was evaluated using DPPH●, ABTS●+, ORAC, and FRAP assays. Powder blends with varying MSN-CAF concentrations (10–70%) were characterized for flow properties (angle of repose, Hausner ratio, Carr’s index), tablets were produced via direct compression, and critical quality attributes (weight uniformity, hardness, friability, disintegration, nanoparticle release) were assessed. MSN-CAF exhibited reduced antioxidant capacity compared with free caffeic acid due to pore entrapment but retained significant activity. Formulation F1 (10% MSN-CAF) showed excellent flowability (angle of repose: 12°, Hausner ratio: 1.16, Carr’s index: 14%), enabling robust tablet production with rapid disintegration, low friability, and complete nanoparticle release in 10 min. Additionally, the antioxidant nanomaterial demonstrated biocompatibility with the HepG2 cell line. MSN-CAF is a versatile nanoexcipient for direct compression tablets, offering potential as an active packaging agent and delivery system in the nutraceutical and food industries.